STRATEGI PEMASARAN POLITIK (POLITICAL MARKETING) DPC PARTAI GERINDRA KOTA SEMARANG DALAM PEMILU LEGISLATIF TAHUN 2014 - Achmad Gufron Kharima; Nur Hidayat Sardini; Fitriyah . (Journal of Politic and Government Studies, 2017)
Gerindra Party is a party that has increased the percentage of votes and seats in the legislative elections in 2014 at the national level, in addition to PDIP which is the party winning the election. At the local level in Semarang City, Gerindra Party also experienced an increase in votes. So the acquisition of Gerindra Party seats in Parliament Semarang City also took part too. The increase of Gerindra Party's vote in Semarang City is an interesting phenomenon to be studied because it has become a new power base considering the political market in Semarang Raya tends to be the basis of nationalist party such as PDIP.In this research use qualitative descriptive analysis method. This study aims to describe and analyze the Political Marketing Strategy of DPC Gerindra Party of Semarang City In Legislative Election Year 2014. With data collection techniques that is, observation, interview and literature study. Informants in this research is the board of DPD Party Gerindra Central Java, board of DPC Party Gerindra Semarang and with the candidates who are directly involved in the legislative election momentum in 2014.Research results show that DPC Gerindra Party of Semarang City has applied the principles of political marketing with good enough to the community. The strategies used also fit the basic political marketing corridor. Commitment and loyalty of the cadre also become the main role in moving the party machine. In addition, the character of Prabowo Subianto who has guerrilla to build the image of Gerindra Party has become one of the success factors of Gerindra Party in Semarang City.Keywords: Gerindra Party, Political Marketing, and Legislative Election Year 2014